Obama's america ebook Unmaking the american dream. - D'Souza, Dinesh (2012)
America as we know it—wealthy, powerful, assertive—is not what Obama wants. He wants a smaller America, a poorer America, an America unable to exert its will, an America happy to be one power among many, an America in decline so that other nations might rise—all in the name of global fairness. To Obama, the hated "one percent" isn't just wealthy Americas; it is America itself. In Obama's view, America needs to be taken down a notch. That is the startling conclusion of bestselling author Dinesh D'Souza in Obama's America . Building on his previous New York Times bestseller The Roots of Obama's Rage —which Newt Gingrich called "Stunning...the most profound insight I have read in the last six years"—D'Souza shows how Obama's goal to downsize America is in plain sight but ignored by everyone. D'Souza lays out what Obama plans to do in a second administration—a makeover of America so drastic that the "shining city on a hill" will become a shantytown in a rather dangerous global village. Arresting in its presentation and sobering in its conclusions, Obama's America is essential reading for those who want to change America's course before it's too late.